Assessment of Flood Discharge Using the HSS SCS–CN Method and Implications for Adaptive Sabo Dam Design in the Saluki River - Yosephina Puspa Setyoasri; Dantje Kardana Natakusumah; Vika Febriyani; Deddy Irwansyah (The University of Lampung, 2026)
In 2018, the Saluki River was morphologically altered due to 7.4 magnitude earthquake. The changes necessitated an evaluation of post-earthquake hydrological conditions prior to Sabo Dam planning. This study aims to estimate the design flood discharge and assess its implications for the preliminary design of a Sabo Dam in Saluki River. Design flood discharge was estimated using the Soil Conservation Service – Curve Number Synthetic Unit Hydrograph (SCS-CN) method. The model results were calibrated using bankfull discharge measured directly. A sensitivity analysis of the CN parameter was performed with ±10% variation to evaluate the effect of post-earthquake changes on peak flood discharge. The design flood discharge was 102.3 m³/s for the 2-year return period (Q2), 143.9 m³/s (Q5), 173.7 m³/s (Q10), 212.8 m³/s (Q25), 244.8 m³/s (Q50), and 272.8 m³/s (Q100). The SCS-CN simulation results deviate only 0.15% from the observed bankfull discharge, indicating that the selected hydrological parameters is in agreement with the characteristics of local rainfall-runoff process and catchment areas in the region. The sensitivity test revealed that a 10% increase in the CN value resulted in a 40% increase in the Q2 peak discharge, while a 10% decrease led to 30% reduction. The Q100 discharge of 272.8 m³/s was adopted as the capacity of Sabo Dam design. In conclusion, SCS–CN method remains applicable for watershed conditions analysis in areas which its morphological changes affected by earthquakes. However, the reliability of the model is constrained by limited field observations and potential uncertainties in CN parameter estimation.